An Econometric Study of the Impact of Public Expenditure on Economic Growth in Algeria Using FMOLS and ECM Models During the Period (1980-2021) - Zakaria Messaoudi, Amel Benali, Houaria Zitouni, Azzi Khalifa, (European Economic Letters (EEL), 2024)
This study aims to highlight the impact of public expenditure on economic growth in Algeria during the period (1980-2021). For this purpose, public expenditures were divided into two variables: equipment and investment expenditures, as well as operating expenditures. The model was formulated using the Fully Modified Ordinary Least Squares (FMOLS) method for the long term, and the Error Correction Model (ECM) for the short term. The study concluded that there is a significant long-term relationship between equipment and investment expenditures and economic growth, while there was no relationship between the variables in the short term. Additionally, the study highlighted an inverse significant relationship between operating expenditures and economic growth in the short term, while there was no relationship between them in the long term.